2013
DOI: 10.1007/s10943-012-9671-0
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking from Clergy and Spiritual Counselors Among Veterans with Depression and PTSD in Primary Care

Abstract: Little is known about the prevalence or predictors of seeking help for depression and PTSD from spiritual counselors and clergy. We describe openness to and actual help-seeking from spiritual counselors among primary care patients with depression. We screened consecutive VA primary care patients for depression; 761 Veterans with probable major depression participated in telephone surveys (at baseline, 7 months, and 18 months). Participants were asked about (1) openness to seeking help for emotional problems fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…Finally, palliative care uses a multi-professional team approach for the treatment of physical, psychological, social and spiritual needs (Palliative Care Definition, WHO 2002). One study involving American veterans found that although nearly 50% of those surveyed reported being somewhat or very likely to seek out help from a spiritual counselor, only 12% actually had contact to a spiritual counselor and 10% had been asked by their VA (Veterans Affairs) providers about spiritual support (Bonner et al 2013). This seems to demonstrate a need for an increased integration of spiritual care providers into the healthcare team as well as training for health care providers in providing spiritual care.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, palliative care uses a multi-professional team approach for the treatment of physical, psychological, social and spiritual needs (Palliative Care Definition, WHO 2002). One study involving American veterans found that although nearly 50% of those surveyed reported being somewhat or very likely to seek out help from a spiritual counselor, only 12% actually had contact to a spiritual counselor and 10% had been asked by their VA (Veterans Affairs) providers about spiritual support (Bonner et al 2013). This seems to demonstrate a need for an increased integration of spiritual care providers into the healthcare team as well as training for health care providers in providing spiritual care.…”
Section: Discussionmentioning
confidence: 99%
“…Chaplains have long been front-line service providers in understanding and caring for Veterans and Service members who are dealing with mental health issues (Bonner et al, 2013; Department of the Army, 2012; Elbogen et al, 2013;Hamilton, Jackson, Abbott, Zullig, & Provenzale, 2011;Zullig et al, 2012), ranging from problems like adjusting to military life or a medical diagnosis to significant psychiatric problems like posttraumatic stress disorder (PTSD), mood disorders, and suicidality. In the extensive 2010 report produced by the DoD Task Force on the Prevention of Suicide by Members of the Armed Forces, chaplains were frequently cited as vital to the prevention of suicide by members of the military (Department of Defense Task Force on the Prevention of Suicide by Members of the Armed Forces, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Veterans and service members may also seek out chaplains because chaplains are able to address salient spiritual dynamics related to depression, posttraumatic stress disorder (PTSD), and other common psychiatric problems. For instance, research suggests that PTSD severity, chronicity, and treatment seeking are often interwoven with issues of guilt, 23,24 forgiveness, 25,26 religious faith, [27][28][29] meaning and purpose, 27,30 and moral injury. [31][32][33] Recognizing that chaplains can be an important part of the mental health care systems for veterans and service members, the Departments of Defense (DoD) and Veterans Affairs (VA) advanced a focus on chaplaincy as part of developing a large-scale, coordinated, cross-departmental vision for attending to the mental health needs of veterans and service members in the post-9/11 era.…”
Section: Introductionmentioning
confidence: 99%